Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Konsumen dalam Pembelian Sembako (Studi Kasus di Pasar Mangkung) - Muliati, Baiq Febrina Dwi; Supriadi (EKBIS : Jurnal Ekonomi & Bisnis, 2025)
The purpose of this study is to know the correlation, double regretion linear among the quality of product and seller of SEMBAKO (the nine basic foods) quality service toward the constumer satiﬁcation at Mangkung traditional market. This is quantitive study by using correlation and double regretion linear analyze. The population of this study are costumers and seller of SEMBAKO and sampels are used 97 womens (housewife). Qusioner was used to take the data. The exfert of judjement was used to validity and reability the instument of this study. Assumption test was conducted before correlation and double regretion linear analyze are applied. The assumtion test were normality and linearity. The result of normality test found only thre variable of normal distribution while the result of linearity test was found the linear data. The correlation test was conducted it caused that ones of the variabel does not has normal distribution, then the result was rejected. This study found that there is a correlation between the quality of product and quality of service toward the cotumers satisﬁcation.